The Role of GAD65 Autoantibodies in the development of Type-1 Diabetes - Sri R. Prasetyo (Fakultas Kedokteran Universitas Kristen Indonesia, 2020)
AbstractThe finding of the autoantibodies to islet cells (ICAs) in type-1 diabetes patients is important for developing the fine tuning of individualized therapy. Antibody to Glutamate decarboxylase 2 (GAD65Ab) is the most reliable sign, since it has the most stable sensitivity as diagnostic tool for detecting type-1diabetes. As a key enzyme in gamma-Aminobutyric acid (GABA) synthesis, GAD65 damage caused by GAD65 antibodies (GAD65Abs) would lead to decrease in the amount of GABA vesicles released by b-cells. Decrease of GAD65 induced by GAD65Ab may endanger the paracrine or autocrine function of GABA, that mediated by γ-aminobutyric acid type A receptors (GABAAR) would depolarized the b-cells. The depolarization then increases intracellular Calsium (Ca2+) concentration that is needed for insulin release. The effect of GABA on b-cells is also important for proliferation and anti-apoptosis of b-cells. Moreover, decrease in GABA release also impairs the inhibiting effect of GABA on T-cell proliferation and inflammatory cytokines release that may end up with escalation of GAD65 damage.Keywords: Type-1 diabetes, autoantibody, GAD65Peran Autoantibodi GAD65 dalam Perkembangan Diabetes Tipe-1AbstractPenemuan autoantibodi terhadap sel pulau atau islet cells (ICA) pada pasien diabetes tipe-1 penting untuk mengembangkan penyesuaian terapi individual. Antibodi terhadap Glutamat dekarboksilase 2 (GAD65Ab) adalah tanda yang paling dapat diandalkan, karena memiliki sensitivitas yang paling stabil sebagai alat diagnostik untuk mendeteksi diabetes tipe-1. Sebagai enzim kunci dalam sintesis asam gamma-aminobutirat (GABA), kerusakan GAD65 yang disebabkan oleh antibodi GAD65 (GAD65Abs) akan menyebabkan penurunan jumlah vesikel GABA yang dilepaskan oleh sel. Penurunan GAD65 yang diinduksi oleh GAD65Ab dapat membahayakan fungsi parakrin atau autokrin GABA, yang dimediasi oleh reseptor asam γ-aminobutirat tipe A (GABAAR) akan mendepolarisasi sel. Depolarisasi kemudian meningkatkan konsentrasi kalsium (Ca2+) intraseluler yang diperlukan untuk pelepasan insulin. Efek GABA pada sel beta juga penting untuk proliferasi dan anti-apoptosis sel beta. Selain itu, penurunan pelepasan GABA juga merusak efek penghambatan GABA pada proliferasi sel T dan pelepasan sitokin inflamasi yang mungkin berakhir dengan peningkatan kerusakan GAD65.Kata kunci: Diabetes tipe-1, autoantibodi, GAD65